Characterization of simian virus 40 on its infectious entry pathway in cells using fluorescence correlation spectroscopy. (26th October 2004) - Bernacchi, S.; Mueller, G.; Langowski, J.; Waldeck, W.
Abstract : SV40 (simian virus 40) is a double-stranded DNA virus and is strongly oncogenic in experimental animals. SV40 enters cells by atypical endocytosis mediated by caveolae, transporting the virus to its usual destination, namely the endoplasmic reticulum. The cellular mechanisms of capsid disassembly (uncoating) and deliverance of the viral genome into the cellular nucleus remain unknown. Here, we study (i) the formation of caveolae after viral infection and the diffusion of caveosome vesicles in the cytoplasm and (ii) the capsid disassembly and the mobility of the viral genome on its way to the nucleus, using fluorescence correlation spectroscopy. To follow the viral genome and capsids separately, the histone components of SV40 minichromosomes were labelled with enhanced yellow fluorescent protein and the capsid was labelled with a fluorescent red dye, Alexa568. We characterized the diffusion of caveosomes, the capsid disassembly process in the cytoplasm and the mobility of the viral genome in the nucleus, using two kinds of permissive cells.